Resynchronization of the left atrium may play an important role in cardiac resynchronization therapy. (3rd October 2022) - Hammersboen, L E R; Aalen, J; Puvrez, A; Larsen, C K; Remme, E W; Donal, E; Duchenne, J; Voigt, J U; Galli, E; Khan, F H; Sletten, O J; Penicka, M; et al.
Abstract: Introduction: Left atrial (LA) dyssynchrony is a predictor of response to cardiac resynchronization therapy (CRT). It is unknown, however, if LA resynchronization contributes to response to CRT. We hypothesize that there is a relationship between correction of LA dyssynchrony and response to CRT. Purpose: To investigate the association between LA resynchronization and response to CRT. Methods: In a prospective study of 171 heart failure patients with LBBB, myocardial strain was measured by speckle-tracking echocardiography, before and 6 months after CRT. As indicated by the white arrows in Figure 1, LA dyssynchrony was measured as the time delay between onset systolic stretch of the interatrial septum and the LA lateral wall. Response to CRT was defined as at least 15% reduction in left ventricular (LV) end systolic volume at 6 months follow up. Results: 119 (70%) patients responded to CRT. The panels in Figure 1 shows LA strain traces in a representative LBBB patient that did respond (upper panels), and a patient that did not respond (lower panels). The white arrows in the left panels indicate that both the responder and the non-responder had marked LA dyssynchrony before CRT (198 and 171 ms, respectively). However, after 6 months with CRT, there was recovery of LA synchrony only in the responder (time delay −40 ms), and still marked LA dyssynchrony of 191 ms in the non-responder (right panels). Figure 2 confirms similar results for the whole study population: CRT response was associated with marked reduction of LA dyssynchrony (p=0.0001). In the CRT non-responders there was, however, only a modest, non-significant reduction of LA dyssynchrony. Conclusions: Positive CRT response was associated with resynchronization of the left atrium. These findings suggest LA resynchronization as a potential additional target for CRT. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Institute for Surgical Research, Oslo University HospitalThe Intervention Centre, Oslo University Hospital